Mortality Within 30 Days After Head and Neck Free Flap Reconstruction: A Systematic Review. Issue 5 (July 2021) - Chicco, Maria; Huang, Tony Chieh-Ting; Cheng, Hsu-Tang
Abstract : Objective: The aim of this systematic review is to analyze the 30-day postoperative mortality in patients undergoing free flap reconstruction for head and neck cancer published in literature and to identify associated factors. Methods: The authors performed a literature search between January 1950 and February 2020 in PubMed, EMBASE, and Scopus, using a combination of Medical Subject Headings headings and text keywords related to head and neck cancer; microsurgery or free flap reconstruction; and 30-day mortality. Inclusion criteria were: original studies in English reporting on 30-day mortality after head and neck free flap reconstruction in adult population. Results: Thirty-one publications reported on a total of 13, 447 patients who underwent head and neck free flap reconstruction. The published 30-day postoperative mortality ranged from 0% to 6.3%, with an average of 1.21%. A number of studies examined the association between mortality and body mass index, American Society of Anesthesiologists, and comorbidity score and age. One study found that underweight patients had significantly higher mortality. Two studies found no association between the American Society of Anesthesiologists score and 30-day postoperative mortality; however, 1 study reported significantly higher mortality with increased comorbidity score. Regarding association with age, 3 studies found significant higher mortality in older patients, while 5 studies found no difference. Conclusions: The average 30-day postoperative mortality in patients undergoing head and neck free flap reconstruction is 1.21% and is; therefore, not negligible. Careful patient selection and preoperative optimization are essential in order to reduce mortality in head neck free flap reconstruction. Abstract : Supplemental Digital Content is available in the text